Doing data: The status of transcripts in Conversation Analysis. (October 2015) - Ayaß, Ruth
This article discusses the status of transcripts in Conversation Analysis. Repeatedly, the function and the epistemic state of transcripts have been the subject of discussions and reflections in Conversation Analysis. Drawing on a range of empirical examples taken from various authors, this article discusses the question of how present forms of visuality and multi-modality in the data material or the handling of artifacts can be captured in transcripts and how the problem of 'representation' of complex and interactive situations can be solved. It turns out that the evolution of recording media along with the medium shift in Conversation Analysis has altered the status of transcripts, effecting a twofold 'in-between-ness': transcripts inhabit the conceptual space between orality and literacy on the one hand and between artwork and figure on the other hand. This oscillating hybrid nature proves to be the central property of transcripts in present-day Conversation Analysis. Transcripts are described as scientific 'objects of knowledge' and discussed with respect to their methodological and epistemic status.